Sondagem de itens de matemática da prova Brasil como instrumento pedagógico na investigação de dificuldades de alunos de 5º ano no município de Boituva/SP - Santos, Markus Pablo Nobre dos (2017)
This quantitative and qualitative research presents as main objective the diagnosis of the difficulties presented by a sample of the 5th year students of the municipality of Boituva/SP in the Mathematics subject based on situations similar to those that are present in the external evaluation denominated Prova Brasil, an important instrument that presents a reading of the Brazilian education. Based on the questionnaires, we drew the profile of these students and their teachers concerning the teaching-learning process. We also elaborated a map of the student's difficulties through the developmental activities done with these students and presented them in this work.